Criminal Sanctions of Unregistered Marriage under Article 402 of Law No. 1 of 2023: Perspectives from Islamic Law and Human Rights - Awwaliyatul Ilmi; Fathullah Rusly; Abd. Hannan (Rechtsvinding, 2026)
Nikah siri (unregistered marriage) is a marriage that fulfills the essential elements and conditions required by Islamic law but is not registered with the competent authority as required by statutory regulations. The enactment of Article 402 of Law Number 1 of 2023 concerning the Criminal Code has generated debate due to the introduction of criminal sanctions related to marriage registration. This study analyzes the criminal sanctions under Article 402 and examines their compatibility with Islamic law and human rights principles. Employing normative legal research with statutory, conceptual, and comparative approaches, the study relies on primary, secondary, and tertiary legal materials analyzed through a descriptive-analytical method. The findings show that the criminal sanctions represent a criminalization policy intended to ensure legal certainty, orderly marriage administration, and the protection of women and children. From the perspective of Islamic law, nikah siri remains religiously valid because it fulfills the essential elements and conditions of marriage, while marriage registration serves as a maslahah instrument consistent with the objectives of Maqasid al-Sharia, particularly the protection of lineage, honor, and property. From a human rights perspective, the regulation is acceptable insofar as its implementation complies with the principles of legality, proportionality, freedom of religion, and the right to form a family. Therefore, Article 402 should be enforced proportionately to balance legal certainty, justice, public interest, and human rights protection